First Demonstration of Double Dissociation between COMT-Met158 and COMT-Val158 Cognitive Performance When Stressed and When Calmer. (30th October 2020) - Zareyan, Shahab; Zhang, Haolu; Wang, Juelu; Song, Weihong; Hampson, Elizabeth; Abbott, David; Diamond, Adele
Abstract: We present here the first evidence of the much-predicted double dissociation between the effect of stress on cognitive skills [executive functions (EFs)] dependent on prefrontal cortex (PFC) by catechol-O-methyltransferase (COMT) genotype. The COMT gene polymorphism with methionine (Met) at codon 158 results in more dopamine (DA) in PFC and generally better EFs, while with valine (Val) at codon 158 the result is less PFC DA and generally poorer EFs. Many have predicted that mild stress, by raising PFC DA levels should aid EFs of COMT-Vals (bringing their PFC DA levels up, closer to optimal) and impair EFs of COMT-Mets (raising their PFC DA levels past optimal). We tested 140 men and women in a within-subject crossover design using extremely mild social evaluative stress. On trials requiring EFs (incongruent trials) of the Flanker/Reverse Flanker task, COMT-Val 158 homozygotes performed better when mildly stressed than when calmer, while COMT-Met 158 carriers performed worse when mildly stressed. Two other teams previously tried to obtain this, but only found stress impairing EFs of COMT-Mets, not improving EFs of COMT-Vals. Perhaps we found both because we used a much milder stressor. Evidently, the bandwidth for stress having a facilitative effect on EFs is exceedingly narrow.